Evaluating the implementation of adult smoking cessation programs in community settings: a scoping review - Mitchell, Remai; O’Grady, Kerry-Ann F.; Brain, David; Lim, Megumi; Bohorquez, Natalia Gonzalez; Halahakone, Ureni; Braithwaite, Simone; Isbel, Joanne; Peardon-Freeman, Shelley; Kennedy, Madonna; Tyack, Zephanie (Frontiers in Public Health, 2025)
IntroductionTobacco smoking is a leading contributor to preventable morbidity and premature mortality globally. Although evidence-based smoking cessation programs have been implemented, there is limited evidence on the application of theories, models, and frameworks (TMFs), and implementation strategies to support such programs. This scoping review mapped the evidence for interventions, TMFs, and implementation strategies used for smoking cessation programs in the community.MethodsWe searched four electronic databases in addition to grey literature and conducted hand-searching between February and December 2023. Original studies of qualitative, quantitative, or mixed methods were considered for inclusion. Studies reporting prospectively planned and/or delivered implementation of smoking cessation interventions or programs, incorporating contextual factors, use of implementation TMF, implementation strategies, or other factors influencing implementation were considered for inclusion. Intervention components were categorized using the Template for Intervention Description and Replication (TIDieR) checklist. Implementation strategies were mapped to the Expert Recommendations for Implementing Change (ERIC) Strategy Clusters.ResultsA total of 31 studies were included. We identified 12 discrete interventions, commonly included as part of multicomponent interventions. Most studies reported tailoring or modifying interventions at the population or individual level. We identified 19 distinct implementation TMFs used to prospectively guide or evaluate implementation in 26 out of 31 included studies. Studies reported diverse implementation strategies. Three studies embedded culturally appropriate TMFs or local cultural guidance into the implementation process. These studies took a collaborative approach with the communities through partnership, participation, cultural tailoring, and community-directed implementation.DiscussionOur findings highlight the methods by which the implementation of smoking cessation may be supported within the community. Whilst there is debate surrounding their necessity, there are practical benefits to applying TMFs for implementing, evaluating, and disseminating findings. We determined that whilst ERIC was well-suited as a framework for guiding the implementation of future smoking cessation programs, there was inconsistent use of implementation strategies across the ERIC domains. Our findings highlight a lack of harmonization in the literature to culturally tailor implementation processes for local communities.